Effect of choir activity in the rehabilitation of aphasia: a blind, randomised, controlled pilot study. Issue 8 (3rd August 2017) - Zumbansen, Anna; Peretz, Isabelle; Anglade, Carole; Bilodeau, Josée; Généreux, Suzanne; Hubert, Michelyne; Hébert, Sylvie
ABSTRACT: Background: Aphasia challenges the functional communication abilities that people use for everyday social interaction. People with non-fluent aphasia struggle to express themselves when speaking, yet they have been shown to better pronounce words when singing familiar songs or novel songs in a choral context. Choral singing and familiar songs are at the core of choir practice, a recreational activity that has long been offered in aphasic associations. Beneficial effects of this activity have been suggested for aphasia rehabilitation but have never been tested in a randomised controlled trial (RCT). Aim: Our study addressed whether the process of such a study is feasible and aimed to provide the first controlled trial of the effects of choir practice on aphasia rehabilitation. Methods: We piloted a three armed-prospective, randomised, parallel-group, open-label, blinded end point (PROBE) pragmatic study with a 1:1:1 allocation ratio and stratification for aphasia severity. The primary outcome was improvement in functional communication. Secondary outcomes included various speech and language skills, mood and quality of life. Participants with chronic aphasia were recruited from five rehabilitation centres and three associations in the greater Montreal area from November 2011 to November 2012. Assessments were carried out by speech and language pathologists before and after a 6-month intervention period where participants had to attend either weekly choir sessions (experimental condition), drama classes (control condition) or neither of these (waiting list). The process feasibility of the design was explored based on rates of recruitment, exclusion, refusal, compliance and completion. Results: Twenty-two participants were recruited and randomised, corresponding to a recruitment rate of 1.8 participant/month. The following rates were measured: Exclusion 40%; Refusal 11%; Compliance 86%; Completion 77%. Changes from pre- to post-activity did not differ significantly between groups in any outcome measure although individual analyses showed various significant changes in different participants. Overall, a significant positive correlation was found between attendance to any social activity and functional communication improvements. Conclusion: A RCT to investigate the effectiveness of choral singing in people with aphasia is feasible. A large sample of people with aphasia is most probably necessary in order to test specific effects of social activities with sufficient statistical power and could be recruited in a large multisite trial. However, prior studies addressing more specifically the scientific (estimating treatment effect and its variance) resources and management feasibility are needed. For now, our results should encourage people with aphasia to participate in social activities in general.